Dna sensor model based on a carbon nanotube network in the degenerate limit - Feiz Abadi, Hediyeh Karimi (2012)
An analytical model of a possible DNA sensor based on a carbon nanotube network that functions as a selective detector of DNA molecules is presented. The ability to implement label-free electronic detection using a DNA sensor based on a carbon nanotube network constitutes an important step towards low-cost, highly sensitive, simple and accurate molecular diagnostics. In particular, there is an urgent need for a simple method of detection of DNA molecules as this will provided a new and efficient way to diagnosis genetic or pathogenic diseases. Bio-compatibility and high sensitivity towards environmental perturbations make graphene nanomaterials a good choice for a sensing layer in an electronic DNA sensor. In this study, a conductance model of a DNA sensor based on a carbon nanotube network is suggested and the performance of the model is evaluated by calculating current-voltage characteristics.